Perceived Risk of Mental Health Problems in Primary Care - Paúl, Constança; Teixeira, Laetitia; Azevedo, Maria João; Alves, Sara; Duarte, Mafalda; O’Caoimh, Rónán; Molloy, William (Frontiers in Aging Neuroscience, 2015)
In the face of limited resources and an ageing population with increasingly care needs, healthcare systems must identify community-dwelling older adults with mental health problems at higher risk of adverse outcomes such as institutionalisation, hospitalisation and death, in order to deliver timely and efficient care. The objectives of this study were to assess the prevalence of mental health concerns and the associated perceived risk of adverse outcomes in a large sample of older patients in primary care. We trained general practitioners and nurses to use the Risk Instrument for Screening in the Community (RISC) to rank perceived risk of mental health concerns (including neurocognitive and mood disorders) from 1 (mild) to 3 (Severe). The mean age of the 4499 people assessed was 76.3 years (sd=7.3) and 2645 (58.8%) were female. According to the primary care team 1616 (35.9%) were perceived to have mental health concerns of whom 847 (52.4%) were mild, 559 (34.6%) were moderate and 210 (13%) were severe. Patients with mental health concerns had higher odds of perceived risk of adverse outcomes (OR=2.22, 95% CI 1.83-2.69 for institutionalisation; OR=1.66, 95% CI 1.41-1.94 for hospitalisation; OR=1.69, 95% CI 1.42-2.01 for death). These results suggest a high prevalence of mental health concerns among older adults and supports the need for early identification of patients at high-risk of adverse healthcare outcomes.